IMPLIKASI FIKIH MUAMALAH TERHADAP LEGALITAS UPAH PENGUMPUL DONASI: Analisis Kritis Transaksi Filantropi Kontemporer - Nasution, Ahmad Ridwan (UIN Sumatera Utara, 2025)
The phenomenon of fundraising for various noble causes is widespread in society. However, the practice of fundraisers taking wages directly from collected donations raises legal questions. This article analyzes the legality of such practices using a normative legal research method (library study) from the perspective of Fiqh Muamalah. The research concludes that it is not permissible to take fundraiser compensation from the donation funds themselves. The principle of Fiqh Muamalah mandates that donation funds must be distributed entirely to the recipients (mustahik). Taking wages is considered to diminish the recipients' rights and potentially violate trust.Consequently, transparency and accountability in donation management are crucial. It is recommended that operational costs or fundraiser compensation be allocated from separate funding sources, or with the explicit consent of donors from the outset. This research provides understanding and guidance for individuals and philanthropic organizations.Keywords: Fundraising, Fundraiser Compensation, Fiqh Muamalah, Islamic Law